A Prospective Study to the Morphological Variation on Radiological Examination (In Form of Appearance of Ossification Centers in Carpal Bones) in Boys and Girls of Age Group 5 to 12 Years of the Western Rajasthan (Jodhpur) Region - Bishnoi, Ramratan; Koodi, Gurusharan (Asian Journal of Medical Research, 2019)
Background: The Determination of age of an individual by radiological observation of the time of appearance and fusion of ossification centers is a matter of great medicolegal and academic interest.In the present study estimation of age in the individual of age varying between 5 year to 12 years will, be conducted using the appearance of ossification of carpal bones in boys and girls of the western Rajasthan (Jodhpur) region.Subjects and Methods:A radiological prospective study done on appearances of ossification centers in the carpal bones inboys and girls of age group 5 years to 12 years in western Rajasthan jodhpur region.Results:There were 50% males and 50% females in the study with male to female ration of 1:1. Precaution was taken to select equal proportion of cases from each half year interval of age among both sexes.Conclusion: We concluded that trapezium, trapezoid and scaphoid carpals appeared between the age of 5 to 9 years.Their appearance was slightly earlier in females than in males.